MOVING A ROBOT HAND TRANSPORTING FILLED GLASS - KOVÁCS-BENDE, M. (Periodica Polytechnica Mechanical Engineering, 1991)
A gripper orientation concept for a robot carrying filled glass along a prescribed path without spilling is presented. The application of the method is shown by a 5-degree freedom high-speed laboratory robot with significant elasticities.